PENGGUNAAN TEAM GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN KEMAMPUAN GRAMMAR MAHASISWA - Lusiana Dewi Kusumayati Sri Handayani Erna Dewi Kartikasari (RESEARCH FAIR UNISRI, 2018)
The purpose of this research are: (1) to explain whether Team Games Tournament is able toimprove students’ grammar competence; (2) to know how far Team Games Tournament canimprove students’ grammar competence; (3) to know the changes of class situation afterimplementing Team Games Tournament in learning grammar. This research wasimplemented in Slamet Riyadi University on March until July 2017. The subjects of thisresearch were the students of semester 4 class 01 Slamet Riyadi University Surakarta inacademic year 2016/2017 which consists of 25 students. The method of this research isclassroom action research. In collecting data, the research used interview, photograph,observation, documents, and field note. The researcher analyzed data using qualitativemethod which consisted of data reduction, data presentation, and conclusion drawing/verification. Besides, quantitative data was analyzed using descriptive statistic. Thisresearch was successful in improving students’ grammar competence. It can be seen fromtheir score in pre test 6.82. it improved to 7.40 in post test 1 and also improved to 8.20 inpost test 2. Besides, the classroom situasion was also improved. The students becamemore active in the classroom. They worked in group enthusiasticly in solving grammarproblems.Kaeywords: Team Games Tournament, Grammar Competence, Classroom Action Research